The Correlation between Body Image Perception and Nutritional Status in Late Adolescent Girls - Siti Husnaini Rizkia; Hurry Mega Insani; Ahdiyatul Fauza; Syifa F. Syihab (Poltekkes Kemenkes Semarang, 2026)
Background: The prevalence of severely underweight and underweight nutritional status among adolescent girls aged 16–18 years in Indonesia increased between 2018 and 2023. The prevalence of severely underweight nutritional status increased by 1.4 times, while the prevalence of underweight nutritional status increased by 1.16 times compared to the previous year. If left unaddressed, these nutritional issues can lead to further nutritional problems, such as Chronic Energy Deficiency. One factor that may influence this condition is the body image perception of these late-adolescent girls themselves. Objective: This study aims to examine the relationship between body image perception and nutritional status in late-adolescent girls. Method: This is a quantitative cross-sectional study using random sampling. The sample size consisted of 67 respondents aged 15–19 years. The data collected included height, weight, and body image perception. The Chi-Square test with a significance level of 0.05 was used to determine the relationship. Results: A total of 74.6% of respondents had normal nutritional status, and 65.7% had moderate body image perception. The Chi-Square test yielded a p-value of 0.011. This indicates a significant relationship between body image perception and the nutritional status of adolescent girls. Conclusion: There is a relationship between body image perception and the nutritional status of adolescent girls.